Performance of Various Organic Solvents as Reaction Media in Plant Oil Lipolysis with Plant Lipase - Astri Nur Istyami; Tatang Hernas Soerawidjaja; Tirto Prakoso; Tri Ari Penia Kresnowati (Reaktor, 2018)
Fatty acids are intermediate substances in synthesis of oleochemical products. Enzymatic technology of fatty acids production (also known as lipolysis) is now developing as potential substitution for the conventional production of fatty acid, i.e. thermal hydrolysis of triglyceride. It offers more economical process condition, low energy consumption, and minimal product degradation compared to the conventional process. This research aims to evaluate performance of various organic solvents as reaction media in lipolysis with plant latex lipase. Organic solvents observed were chloroform, n-hexane, diethyl ether, benzene, acetone, ethanol, methanol, n-heptane, and isooctane. Analysis of each organic solvent effect on lipolysis was described based on solvents properties. Conversion of lipolysis with organic solvents is 0,10-1,25 times fold compared to conversion of non-solvent lipolysis. We suggest that dielectric constant and viscosity are the two main organic solvent properties affecting lipase performance in lipolysis. Overall, n-hexane, n-heptane, and isooctane are recommended to be used as reaction media in lipolysis with plant lipase because their effects to degree of lipolysis are positive.  Keywords: lipolysis; lipase; organic solvent; frangipani